Proceedings of the 2014 International Conference on Global Economy, Commerce and Service Science 2014
DOI: 10.2991/gecss-14.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Formation Mechanism of Revisit Intention: Data from East China

Abstract: Abstract-The paper discusses the factors of revisit intention, and constructs an Extended Model of TPB which contains the variables of attitude, customer's value etc. Based upon the literature review, the paper constructs the measurement of these factors. The structured survey is adapted to encompass four different destination types and the data is analyzed through SEM to research the formation mechanism of revisit intention. The results demonstrate that subjective norm, behavior control perception, attitude, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Satisfaction in value perception effects tourists' intention to re-visit. This is in line with research by Sweeney and Souter (2010), Chang (2013) and Li (2014) who stated that value perception has a significant effect on customer's satisfaction. Based on these findings, this research hypothesis is:…”
Section: The Relationship Between Value Perception and Customer's Satsupporting
confidence: 91%
“…Satisfaction in value perception effects tourists' intention to re-visit. This is in line with research by Sweeney and Souter (2010), Chang (2013) and Li (2014) who stated that value perception has a significant effect on customer's satisfaction. Based on these findings, this research hypothesis is:…”
Section: The Relationship Between Value Perception and Customer's Satsupporting
confidence: 91%
“…The positive word-of-mouth of repeated tourists are considered as the best marketing tool (Chin et al, 2018;Som & Badarneh, 2011) and as such, a number of studies have found that revisit intention represented the loyalty of customers that intend to revisit the destination, destination image also a key indicator influence tourist to choose the same destination as future intention to visit (Chi & Qu, 2008;Stylidis et al, 2017). Due to the competitive tourism market, tourists' positive experience from past travel such as quality of service and product play a crucial role on creating tourists' revisit intention to tourism destination (Choo et al, 2016;Li, 2014;Tubey & Tubey, 2014).…”
Section: Revisit Intentionmentioning
confidence: 99%
“…The concept of Revisit intention comes from a customer behavior study which is essentially a repurchase decision, but there are differences between the tourist decision-making process and the consumer decision-making process in other products, because tourists cannot feel the product before buying [23]. From the perspective of the buying process, tourist behavior is divided into three stages, including: previsit, during visit, and post-visit [11].…”
Section: B Revisit Intentionmentioning
confidence: 99%